Heterotopic gastric mucosa of upper esophagus: evaluation of 12 cases during gastroscopic examination - Oymaci, Erkan; Cengiz, Fevzi; Ucar, Ahmet Deniz; Erkan, Nazif; Yildirim, Mehmet (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction: Oesophageal heterotopic gastric mucosa mostly presents in the upper part of the oesophagus. It is commonly under-diagnosed because of its localisation. Aim: To expose the association between heterotopic gastric mucosa and endoscopic features of the upper gastrointestinal tract. Material and methods : A total of 1860 upper endoscopic examinations performed between January 2012 and July 2013 were analysed retrospectively. Endoscopic features and histological examinations of 12 heterotopic gastric mucosa (HGM) of the upper oesophagus were documented and evaluated retrospectively. Results: There were 7 (58%) male and 5 (42%) female patients aged between 22 and 80 years with a mean age of 43.2 years. Heterotopic gastric mucosa was present in 12 (0.6%) of all patients. We were able to perform biopsy for histopathological observation on 8 (66%) of the 12 patients in which HGM was seen during endoscopy. Five (42%) patients with heterotopic gastric mucosa had oesophagitis. Los Angeles Grade A oesophagitis was found in all patients, and histologically proven Barrett’s oesophagus was detected in only one patient. Conclusions : When a patient has ongoing dyspeptic complaints and reflux symptoms despite the treatment, one should be careful about possible HGM during upper gastrointestinal endoscopy. The point to be taken into consideration for patients who have metaplasia or dysplasia within HGM may need to be considered for surveillance.